Consumer Involvement for QR Code Applications, the Digital DNA of Brands - Çakırkaya, Murat; Koçyiğit, Murat (International Journal of Contemporary Economics and Administrative Sciences, 2024)
The purpose of the research is to determine the relationship between consumer involvement in QR code applications, and purchasing decision involvement and the effect level of this relationship. Generation Z consumers constitute the population of the research. Since it was not possible to reach the entire generation Z within the scope of the research, the research was carried out using the purposeful sampling method, which is one of the non-probability sampling types. The research was conducted online, and the relationships between variables were tested over the data of 394 people participating in the study, and the accuracy of the hypotheses formed was tested. In the analysis of the data, descriptive statistics, correlation analysis and multiple linear regression analysis were performed using the statistical package program. As a result of the research, it was determined that there is a moderate and significant (p<0,001) relationship between the variables of “hedonic value” (r=,575; p=,000) and “perception towards the brand” (r=,643; p=,000), and the “purchase decision involvement” variable, which are sub-dimensions of consumer involvement towards QR code applications. At the same time, it is another result of the research that the variables of “hedonic value” and “brand perception”, have a statistically significant effect on the purchasing decision.